Perceptions of senior nursing students on how the COVID-19 pandemic influenced their clinical practice in the Northwest Province, South Africa: a qualitative study - Sofia Fatima Filomena Apolinario; Edith Nokwanda Bam; Miriam Moagi (BMJ Open, 2024)
Objective To explore and describe senior nursing students’ perspectives on clinical practice during COVID-19 and provide the most up-to-date information on the quality of clinical experience for nursing students in relation to nursing practice, nursing education, and nursing research.Design The research design that was employed is a qualitative, explorative, descriptive in order to explore and describe nursing students’ perceptions of clinical, training during the COVID-19 pandemic.Setting The study took place in a local university located in the Northwest province, South Africa.Participants The population consisted of 16 senior nursing students who had been exposed to clinical practice during the COVID-19 pandemic. There were 14 women and 2 men. Study included full-time, registered undergraduate nursing students who enrolled in 2019. All nursing students who did not engage in clinical practice before or during COVID-19 were exempt.Interventions There were no direct interventions in this study; however, few recommendations were made for each of the themes that emerged in this study.Primary and secondary outcome measures The researchers’ aim with the study was to find out the nursing students’ perspective on clinical training during a global pandemic, through interviews and focus group discussions. The researcher did in fact receive such feedback from the participants.Results Four major themes emerged: (1) the lack of preceptors to facilitate clinical teaching; (2) not allowed to work in COVID-19 wards; (3) difficulties with online classes and tests and (4) poor communication.Conclusion The COVID-19 pandemic influenced how students viewed and experienced clinical training, which in turn had an impact on their learning experiences. These effects also had some impact on their experiences and decisions to continue working as professional nurses.